Effects of mental fatigue on biomechanical characteristics and risk associated with non-contact anterior cruciate ligament injuries during landing - Zheng, Bosong; Zhang, Zeyang; Zhang, Zeyi; Sun, Youping; Xiao, Yao; Li, Mengjie (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate and compare the effects of mental fatigue (MF) on biomechanical characteristics associated with non-contact anterior cruciate ligament injury (NC-ACLI) in male college students during stop-jump (SJ) and single-leg landing (SL), and whether it increases NC-ACLI risk.MethodsMF was induced by a 45-min Stroop task and measured using the visual analogue scale for MF (VAS-MF), while motion capture, force platforms, and surface electromyography (SEMG) evaluated biomechanical variables before and after MF induction in thirty-six subjects. Kinematic, kinetic, and SEMG data were analyzed using two-factor repeated measures ANOVA and rank-based nonparametric ANOVA.ResultsFollowing MF induction, VAS-MF scores increased significantly. The ANOVA showed that in both maneuvers, peak vertical ground reaction force increased, while ankle dorsiflexion angle and knee flexion moment decreased. In SJ, knee flexion and internal rotation angles and internal rotation moment decreased, whereas knee abduction moment increased; these parameters did not change significantly in SL. The median frequency of biceps femoris SEMG decreased in SL but remained unchanged in SJ. No significant differences were found in hip flexion angle, knee adduction angle, or SEMG measures of rectus femoris, tibialis anterior, gastrocnemius lateral head, or biceps femoris root mean square.ConclusionMF partly influences NC-ACLI biomechanics and increases risk in both maneuvers—more pronounced in SJ than in SL—potentially due to MF’s impact on central nervous system function, cognition, and attention. MF should be considered in NC-ACLI prevention strategies.